The evolutionary characteristics and neighbourhood mechanisms of urban innovation networks: The case of China's sports industry. - Kun Peng; Yimeng Ma; Laibing Lu; Dangsheng Wang; Dong Zhu (PLoS ONE)
Taking the patents granted from 2006 to 2023 and the applicants located in different cities in China as data samples, with the help of UCINET 6.0 software and according to the timeline, we visualise the cooperation and innovation network of the sports industry during the period of the "11th Five-Year Plan" to the "14th Five-Year Plan". QAP multiple regression analysis was used to explore the impact of geographical, cognitive, institutional, economic, and technological proximity on the collaborative innovation performance of the sports industry at different stages.The research results indicate that (1) The scale of China's sports industry cooperation and innovation network continues to expand, the cohesion of the network is constantly strengthening, and the complexity of regional cooperation relationships is gradually increasing, forming a grid-based cooperation trend with multiple innovative entities from the early "one place leading" model; (2) From 2006 to 2015, innovation cooperation in the sports industry was more likely to occur between geographically adjacent regions. Since 2016, innovation cooperation in the sports industry has gradually broken geographical limitations. In addition, since 2011, the level of knowledge sharing among sports technology innovation entities in various cities in China has further deepened, the gap in cognitive ability has intensified the efficiency of cooperation between different innovation entities, and innovation cooperation is concentrated between cities with comparable economic strength. Starting from the "14th Five Year Plan" period, cooperation between cities with similar innovative technological capabilities has become closer, and the efficiency of innovation output has significantly improved.